Evaluation of the Anti-Psoriatic Effect of Topical Dovramilast in an Imiquimod-Induced Psoriasis Mouse Model - Suhail, Hasnaa; Hameed, Mohameed Fareed (Journal of Pharmacology and Drug Development, 2026)
​ Objective: The aim of the study is to determine the pharmacological effect of phosphodiesterase 4 inhibitor (dovramilast) in a psoriasis mice model induced by imiquimod, and to estimate the levels of pro-inflammatory cytokines in skin tissue (IL-17A, IL-23 and TNF-α). Furthermore, histopathological scores for skin tissue were determined. Methods: Fifty BALB/c male albino mice aged 8 weeks were used in this study. The mice were classified into five groups each group contain ten mice (n=10) as the following, group I (control) contained healthy mice, group II (induction) involve application of imiquimod 5% cream once daily for five consecutive days to produce inflammatory lesions that resemble to plaque psoriasis, group III, IV and V involve application of imiquimod 5% cream then three hours later treatments were applied for five consecutive days were, group III received clobetasol 0.05% ointment, group IV received dovramilast 0.3% ointment and group V utilize combination of formula contain both dovramilast 0.15% with clobetasol 0.025% ointment. Results: The dovramilast-treated group showed a significant reduction in all inflammatory cytokines (IL-17A, IL-23 and TNF-α) compared to induction (P